LncRNA NR038975, A Serum-Based Biomarker, Promotes Gastric Tumorigenesis by Interacting With NF90/NF45 Complex - Wei, Sisi; Dai, Suli; Zhang, Cong; Zhao, Ruinian; Zhao, Zitong; Song, Yongmei; Shan, Baoen; Zhao, Lianmei (Frontiers in Oncology, 2021)
Gastric cancer (GC) is one of the deadliest cancers, and long noncoding RNAs (LncRNAs) have been reported to be the important regulators during the occurrence and development of GC. The present study identified a novel and functional lncRNA in gastric cancer, named NR038975, which was confirmed to be markedly upregulated in the Gene Expression Profiling Interactive Analysis (GEPIA) dataset and the independent cohort of gastric cancer tissues. We firstly characterized the full-length sequence and subcellular location of NR038975 in gastric cancer cells. Our data demonstrated that upregulated NR038975 expression was significantly related to lymph node metastasis and TNM stage. In addition, knockdown of NR038975 inhibited gastric cancer cell proliferation, migration, invasion and clonogenicity, and vice versa. Mechanistically, RNA pull-down and mass spectrometry assays identified the NR038975 binding proteins, NF90/NF45 complex, and the binding were also confirmed by RNA immunoprecipitation and confocal experiments. We further demonstrated that genetic deficiency of NR038975 abrogated the interaction between NF45 and NF90. Moreover, NF90 increased the stability of NR038975. Thus, NR038975-NF90/NF45 will be an important combinational target of GC. Finally, we detected NR038975 in serum exosomes and serum of gastric cancer patients. Our results indicated that NR038975 was a biomarker for gastric tumorigenesis. The current study demonstrated that NR038975 is a novel lnRNA that is clinically and functionally engaged in the gastric cancer progression and might be a novel diagnostic marker and potential therapeutic target.